2022
DOI: 10.1057/s41599-022-01225-1
|View full text |Cite
|
Sign up to set email alerts
|

Virtual tree, real impact: how simulated worlds associate with the perception of limited resources

Abstract: Video games have long been considered an effective educational tool. Environmental education studies have found that games positively affect the feeling of nature connectedness, producing pro-environmental attitudes and behaviors. With growing urbanization, video games also provide chances to interact with nature. During the COVID-19 lockdown, Nintendo’s Animal Crossing: New Horizon (ACNH) became a household name, with millions of copies sold worldwide. The article used the Bayesian multilevel model to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Cumbo and Iversen (2020) recommend digital tools like video games to promote long‐term environmental stewardship in children. Ho et al (2022) have expressed similar conclusions about the limitation of natural resources. Thus, we believe that games focused on natural environment such as AC could give an answer to Soga et al (2020) about the mitigation of biophobia through natural experience in children.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Cumbo and Iversen (2020) recommend digital tools like video games to promote long‐term environmental stewardship in children. Ho et al (2022) have expressed similar conclusions about the limitation of natural resources. Thus, we believe that games focused on natural environment such as AC could give an answer to Soga et al (2020) about the mitigation of biophobia through natural experience in children.…”
Section: Discussionmentioning
confidence: 71%
“…As it has been suggested for several video games in empirical studies, including AC, this video game could be a tool to learn ecological concepts and conservation threats (Balmford et al, 2002;Fisher et al, 2021;Genovart et al, 2013). Ho et al (2022) have analyzed survey responses of 640 AC players and found that AC video games could impact players' environmental perception around the topic of limitation of resources. Nevertheless, no previous studies have quantitatively investigated how AC video games might contribute to taxonomic knowledge and education.…”
Section: Introductionmentioning
confidence: 99%
“…In a teenage audience, it is possible that raising awareness about these sexist attitudes present in an environment so close to them, such as video games, may cause gamers to reflect on issues related to discrimination, sexualization, and gender stereotypes in a way that may not otherwise be possible, all of which may encourage them to reject sexism in real life. For example, in a virtual world that illustrates real-world problems, gamers also learn about environmental issues and the solutions to address or mitigate them (e.g., Ho et al, 2022; Meya & Eisenack, 2018). In other words, reducing this gender inequality will benefit society as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used life simulation games such as the SIMS 4 in educational settings such as language, gender, and cultural studies [4] [19] [61] and Second Life where researchers facilitated a co-creation system to design stimulating user experiences within the platform [38]. Simulation games provide a way for people to learn about and experience the world through an alternative perspective gaining an understanding of language, social relations, cultural and environmental issues [56] [32]. Many of the studies on simulation video gaming or serious games have found that using virtual reality in addition to the game to depict the past or enact potential scenarios, such as in emergency response training create an immersive embodied experience that can aid empathy and a connection to alternative experiences [29] [41] .…”
Section: Related Workmentioning
confidence: 99%